(untitled) (VERUM: Journal of Scientific Initiation, 2026)
Exhaustion, depression, and irritability have undermined the emotional well-being of teachers, leading to both physical and mental health issues. Among the various causes affecting them in the workplace are the daily demands and pressures inherent to their profession. Within this context, the study aimed to evaluate occupational stress in the school environment from the perspective of teachers and students in public schools in the municipality of Maranguape, Ceará. The research involved the collaboration of Science teachers from this municipality and students from the 6th and 9th grades of lower secondary education. This descriptive study collected data through questionnaires administered to both groups (teachers and students). The findings indicate that while most teachers feel willing to carry out their teaching duties, they experience a high degree of emotional exhaustion, with symptoms occurring more frequently in some than in others. Students, on the other hand, reported having a positive relationship with their teachers, describing them as attentive and kind. The majority stated that they did not perceive irritability from their teachers. It was observed that teachers are demotivated and stressed, yet they do not display their dissatisfaction to students. These results highlight the urgent need for greater recognition and respect for the teaching profession.